Gedanken zur Erzählprosa Herman Kestens - Schlosser, Jan (Nordlit, 2006)
The article focuses on the topic of identity crisis in the short stories of German author Hermann Kesten. He presents no ideological solution of the identity problem, which is reflected in an anthropological dimension, but has a distinct preference for joie de vivre.
Keywords: Hermann Kesten; Identitätsverlust; Entfremdung; Lebenslust; Schmerz; Antisemitismus; Anthropologie; Fortschrittsglaube